Effects of shoulder injury prevention strength training program on throwing effectiveness - Andrade, M. S.; Mascarin, N. C.; Silva, A. C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
As a result of repetitive throwing motion, the concentrically activated internal rotator (IR) muscles significantly increase in strength, which may not be accompanied by a proportionally increase in external rotator (ER) muscles strength. These disproportional strength gains cause shoulder rotator muscles imbalance, which has been found to be a primary risk factor for glenohumeral joint injuries (Forthomme et al 2005). This adaptive imbalance may be beneficial for throwing performance. Therefore, the aim of this study was to verify if a strengthening program directed to correct adaptive strength imbalance may influence throwing effectiveness. Methods: Twentyeight female handball players were assigned to either an experimental group [EG, (n=16)] or a control group [CG, (n=12)]. EG athletes included in their usual training schedule 6 wk of individual progressive strength training program (STP), 3 times a wk. CG athletes performed only the usual training sessions. Athletes performed strength tests on an isokinetic dynamometer. IR and ER muscles peak torque (PT) values were evaluated at angular velocities of 60./s and 240./s in the concentric (con) mode and at 240./s in eccentric (ecc) mode. Based on ERcon/IRcon and ERecc /IRcon peak torque ratios a preventive STP was developed. Athletes performed 2 tests to assess ball velocity and accuracy throwing. Tests consisted of 5 jumping or 5 standing shots on the spot towards a target from 7 m distance. The mean of 5 throws was calculated. Both tests were performed before and after the intervention. Results: STP improved ER and IR PT (60o/s) values in EG (p<0.05) but not in CG. There were no significant differences for shoulder rotator muscle imbalance before and after STP for both groups, even though mean values for muscular imbalance were closer to those values suggested by previous studies. After STP throwing ball velocity was significantly higher in EG than in CG (p=0.006). There were no significant changes on aiming accuracy. Discussion: Although Zapartidis et al (2007) have demonstrated that ER and IR PT values were not related to ball velocity the present study showed significantly higher ball velocities after STP in EG. Therefore, data suggest that STP is effective to increase muscular rotator strength, to correct shoulder muscle imbalance and to increase throwing ball velocity, without producing harmful effects on aiming accuracy.